Nurses’ Knowledge and Practices Regarding Oxytocin Administration in the First Stage of Labor in Maternity Teaching Hospital in Sulaimaniyah City - Faris, Gona Othman (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Oxytocic refers to a group of drugs that cause contraction of uterine muscles, resulting in the delivery of the placenta or fetus. As an oxytocic agent, oxytocin is a serious and significant medication that is broadly utilized in clinical practice to help with the initiation and continuation of labor. Failure to use oxytocin properly can lead to serious adverse impacts on both mother and baby; therefore, health professionals need to pay close attention during its administration. Materials and methods: Through a descriptive analytical study conducted at the labor and delivery unit in Maternity Teaching Hospital in Sulaimani city, the nurses’ knowledge and practice regarding oxytocin administration during the 1st stage of labor were assessed. A convenient sampling method was employed to all (70) nurses working in the labor room from 5th January to 20th February 2022. Data collection was carried out through 3 tools, including a structured interview questionnaire which was aimed at gathering the nurses’ general characteristics, a nurses’ knowledge questionnaire, and an observational checklist to assess the nurses’ practices regarding oxytocin administration. Statistical Package for the Social Sciences version (version 22.0) was used to analyze the collected data. Results: The results indicated that the nurses’ level of knowledge and oxytocin administration practice was below average in 60.0% and 45.7% of them, respectively. It was also seen that the knowledge and practice were poor in half of the nurses. Moreover, there was a positive correlation between total knowledge and practice scores. Conclusion: Based on the findings of the present study, it is recommended that periodic in-services training programs should be conducted for the nurses who administer oxytocin drugs in order to constantly improve their knowledge and practice of safe administration and to reduce the adverse impacts of this drug.
Keywords: Assessment; Oxytocin administration; Nurses; Knowledge and practice